Place of lung resection in the treatment of hydatic cyst of the lung - Rubio, Roberto; Matteucci, Pablo (Cirugía del Uruguay, 2020)
Recent developments in the surgical treatment of pulmonary hyalin hydatids, either open or vomited, are discussed.